Enhancing Transportation Route Optimization Through Genetic Algorithm-Based Vehicle Routing Problem Method - Sidiq Syamsul Hidayat; Bagaskara Bagaskara; Amin Suharjono; Irfan Mujahidin (Scientific Journal of Informatics, 2023)
Purpose: The purpose of this study is to identify effective and efficient waste collection route for cost savings. The focus is on Tembalang District, where waste management has been compromised due to inefficient transportation.Methods: The study employs genetic algorithm to ascertain the optimal routes for waste collection vehicles. This method seeks to design an improved transportation system, taking waste from transfer stations (TPS) to landfills.Results: The devised waste transport model from the study demonstrated an optimized route for Tembalang Sub-District, with a total distance of 17.90 km and took 49 minutes. This contrasts with the existing route defined by the Sanitation Department, which spans 18.20 km and requires 1 hour and 15 minutes.Novelty: Innovative application of the Vehicle Routing Problem method coupled with the Genetic Algorithm. This approach resulted in a significant reduction of time (by 35%) compared to traditional routing systems, and thus minimizing the number of waste collection vehicles required and enhancing overall waste management in Semarang.